Mathematics
RonnieMarie
2021-09-15 03:27:45
A system of equations is shown below: -3x + 7y = -16 -9x + 5y = 16 Part A: Create an equivalent system of equations by replacing one equation with the sum of that equation and a multiple of the other. Show the steps to do this. (6 points) Part B: Show that the equivalent system has the same solution as the original system of equations.
ANSWERS
lilyellis32
2021-09-15 06:22:33

  -3x + 7y = -16 - 9x + 5y = 16 + 9x                  + 9x           + 9x    6x + 7y = -16 + 5y = 16 + 9x          - 5y           - 5y          - 5y    6x + 2y = -16 = 16 + 9x - 5y         + 16  + 16 + 16                  6x + 2y + 16 = 9x - 5y  - 6x                 - 6x                  2y + 16 = 3x - 5y        + 5y                + 5y           7y + 16 = 3x                - 16  - 16                   7y = 3x - 16                    7          7                     y = ³/₇x - 2²/₇

ADD ANSWER